Morphological characterisation of the coronary arteries in African sheep (Ovis orientalis). Differential analysis with those of humans and other animal species (2019)
Background: Despite the importance of the coronary system in the African sheep as a possible experimental model, there is little information about this particular vascular system. The objective of this investigation was to characterise morpho-logically the coronary arteries and their branches in African sheep. Materials and methods: This descriptive cross-sectional study evaluated the coronary arteries and their branches of 62 hearts of short hair sheep. The right and left coronary ostia were perfused with a semi-synthetic resin (Palatal GP40L 85%; styrene 15%) dyed with mineral red. The morphological characteristics were evaluated using a digital calibrator and the biometrics of the coronary arteries and their branches were registered. Results: The right coronary artery had a proximal calibre of 2.11 ± 0.46 mm. The subsinusal interventricular branch ended at the middle third of the homonym sulcus in 19 (30.6%) specimens. The left coronary artery had a diameter of 5.38 ± ± 1.59 mm and a length of 4.67 ± 3.32 mm. This artery bifurcated itself in the paraconal interventricular branch and the left circumflex branch in 57 (91.9%) hearts and trifurcated with an additional left diagonal branch in 5 (8.1%) spec-imens. Left coronary artery dominance was observed in 51 (82.3%) specimens, whereas in 11 (17.7%) cases the coronary circulation dominance was balanced. Conclusions: Due to the similitude in the features of the coronary arteries between African sheep and humans, this animal model can be proposed for procedural and haemodynamic activities. Copyright © 2019 Via Medica.